Meningkatkan Aktivitas Dan Prestasi Belajar Seni Kriya Dengan Model Pembelajaran Problem Based Learning Pada Siswa Kelas XI IPS 1 SMA Negeri 1 Manggis - I Nyoman Sukadana (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2019)
This study aims to (1) find out how much activity and learning outcomes of students of class XI IPS 1 SMA 1 Manggis can be improved by applying Problem Based Learning Learning Model (2) knowing and describing the responses of students of class XI IPS SMA 1 Manggis to the application of models learning problem based learning. This type of research is classroom action research consisting of two cycles. Each cycle consists of planning, action, observation / evaluation, and reflection. The subjects of this study were students of Class XI IPS 1 in the Senior High School 1 Manggis 2017-2018 Academic Year as many as 30 people. Student activity data was collected through an observation sheet consisting of 6 indicators, each of which included 4 descriptors, data on student learning outcomes were collected through a test in the form of a description, and data on student responses collected through questionnaires. The collected data were analyzed using descriptive analysis. The results showed that the application of the Based Learning Learning Model was able to improve learning activities from the criteria of "quite active" in the first cycle to be "active" in the second cycle, namely from the average score of 18.0 to 19.4 and able to improve learning achievement from the score on average 75.0 at pre cycle to 84.3 in cycle I and 90.0 in cycle II with increased absorption from 75.00% at pre-cycle to 84.03% in cycle I and 90.00% in cycle II and the level of learning completeness from 75.00% during the pre-cycle to 86.70% in the first cycle and 96.70% in the second cycle. Students give a positive response to the application of the Problem Based Learning Learning Model with an average score of 90.0%.